2016
DOI: 10.15740/has/irjaes/7.1/86-90
|View full text |Cite
|
Sign up to set email alerts
|

Economics and constraint analysis of non traditional maize farmers in Mahbubnagar district under Tank of Andhra Pradesh

Abstract: : This paper has been drawn from part of work done by the authors to assist Varsha NGO, Hyderabad in project on the value chain analysis of maize with an objective to study the economics of maize farmers cultivating under tank irrigation and constraints faced by them in Mahbubnagar district. The study showed that out of total cost of cultivation of Rs. 32041.23 per hectare, the operational costs contributed 84.41 per cent and the remaining 15.59 per cent by fixed costs. Farmers secured a net benefit cost ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…As the overall cost of spring maize cultivation was ` 83350 ha -1 , the net returns derived out to be ` 24679 ha -1 in the study area. Similar results of spring maize profitability were narrated by Devi and Suhasini, (2016); Singh et al (2018); Saeed et al (2018) and Choudhri et al (2018) in their studies. Further, similar findings were also reported by Ghimire et al (2016) while conducting a field experiment on 'Rajkumar' variety of spring maize cultivated using improved practices in Bardiya district of Nepal.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…As the overall cost of spring maize cultivation was ` 83350 ha -1 , the net returns derived out to be ` 24679 ha -1 in the study area. Similar results of spring maize profitability were narrated by Devi and Suhasini, (2016); Singh et al (2018); Saeed et al (2018) and Choudhri et al (2018) in their studies. Further, similar findings were also reported by Ghimire et al (2016) while conducting a field experiment on 'Rajkumar' variety of spring maize cultivated using improved practices in Bardiya district of Nepal.…”
Section: Resultssupporting
confidence: 87%
“…It is largely utilized for three purposes i.e. as a human staple meal, livestock feed and industrial raw material (Devi and Suhasini, 2016). With potential growth rate in various maize-based industries such as feed sector (8%), starch industry (5.1%), ethanol industry (12.5%), processed food industry (11.5%) and dairy sector (4.5%), the cumulative demand for maize will reach to 43 million tonnes by 2030 (Rakshit et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…indicates that, the cost of cultivation of maize per hectare in marginal size group is higher than small and semi-medium farm groups. Similar study conducted by [8] revealed that, increase in cost of production mainly due to increase in prices of labour and inputs used.…”
Section: Cost Of Cultivation For Irrigated Maizesupporting
confidence: 60%
“…A value chain mapping is carried out to comprehend the various stakeholders, how they are interconnected, and how each plays a specific role. The actors of the value chain, their roles, and linkages were shown in the format of figure [16]. The value chain includes numerous operations, including preproduction (supply of inputs), industrial processing, and marketing of finished items to consumers [17&18].…”
Section: Resultsmentioning
confidence: 99%